Republic of Armenia : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
This paper evaluates the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) for Armenia, which builds on the strategy laid out in the Interim PRSP. It provides an extensive analysis on the causes of poverty and the challenges faced, the comprehensive strategy with short- and long-term perspectives, set of public actions, evaluation plans, costing of programs, and the financing scenario. It also reviews planning, implementation, monitoring, and evaluation of the strategy.